Forced Repossession of Vehicles by Debt Collectors and Its Implications for Consumer Protection after the Constitutional Court Decision No. 18/PUU-XVII/2019 - Susanto, Alfinto Rizky; Rifa’i, Muhammad Rifqi; Muhaimin, Ahmad; Hamidan, Friska Nova; Sahwal, Muhammad; Ifaza, Savina Distya (Rechtsvinding, 2025)
Forced repossession of vehicles by debt collectors in public spaces continues to occur despite the Constitutional Court Decision Number 18/PUU-XVII/2019, which affirms that the execution of fiduciary security may not be carried out unilaterally and must follow lawful procedures. This situation creates legal uncertainty for consumers and increases the risk of intimidation and violence in financing practices. This article examines the implications of the decision for consumer protection and law enforcement by assessing the gap between legal norms and practices in the field. This study employs a normative juridical method by analyzing statutory regulations, court decisions, and comparative evaluations of repossession practices, supported by mass media information and regulatory reports from Otoritas Jasa Keuangan (OJK) and Badan Perlindungan Konsumen Nasional (BPKN). The findings indicate that the Constitutional Court’s decision has transformed fiduciary execution by restricting creditors from forcibly seizing vehicles from debtors; however, weak supervision, limited understanding among law enforcement officials, and the involvement of uncertified third-party debt collectors continue to create opportunities for forced repossession practices. This study concretely identifies a gap between the provisions of Constitutional Court Decision No. 18/PUU-XVII/2019 and field practices, as forced repossession by debt collectors still occurs despite the requirement that fiduciary execution be conducted through the debtor’s consent or a court order. This gap arises from the absence of national standard operating procedures for law enforcement officers, weak oversight by the OJK over the use of debt collectors, limited police understanding of fiduciary execution, and low levels of consumer legal literacy. Therefore, this study emphasizes the need for technical regulations governing the operational procedures of fiduciary execution and the strict enforcement of administrative sanctions, including fines, license suspension, and operational bans, to ensure that constitutional provisions are implemented effectively and consistently in practice.